2022
DOI: 10.1021/acsphotonics.2c00626
|View full text |Cite
|
Sign up to set email alerts
|

Single-Frame Characterization of Ultrafast Pulses with Spatiotemporal Orbital Angular Momentum

Abstract: Light carrying spatiotemporal orbital angular momentum (ST-OAM) makes possible new types of optical vortices arising from transverse OAM. ST-OAM pulses exhibit novel properties during propagation, transmission, refraction, diffraction, and nonlinear conversion, attracting growing experimental and theoretical interest and studies. However, one major challenge is the lack of a simple and straightforward method for characterizing ultrafast ST-OAM pulses. Using spatially-resolved spectral interferometry, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Recently, researchers have exploited spatiotemporal differentiators based on metasurfaces [66][67][68] and multilayered structures, [69] which are much more compact than traditional pulse shapers [70,74,75] with indispensable spatiotemporal Fourier transform components, to generate spatiotemporal optical vortices (STOVs) with transverse OAM. In Section S2 (Supporting Information), we show that our first-order spatiotemporal differentiator can not only give rise to the spatial and temporal profiles of a single rectangular-shape pulse input but also stamps a transverse OAM with a fractal topology charge number (l = 0.58) for the output pulse.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have exploited spatiotemporal differentiators based on metasurfaces [66][67][68] and multilayered structures, [69] which are much more compact than traditional pulse shapers [70,74,75] with indispensable spatiotemporal Fourier transform components, to generate spatiotemporal optical vortices (STOVs) with transverse OAM. In Section S2 (Supporting Information), we show that our first-order spatiotemporal differentiator can not only give rise to the spatial and temporal profiles of a single rectangular-shape pulse input but also stamps a transverse OAM with a fractal topology charge number (l = 0.58) for the output pulse.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3c, the value and sign of the topological charge were reflected as the number of lobes and the stretched direction of the measured diffraction patterns in the x−y plane, respectively. Guan Gui et al 26 demonstrated that, by introducing an extra reference pulse in the diffraction method, the resulting interference fringes could be used to fully characterize ST vortices with a single frame, while also not requiring strong pulse energy (Figure 3d). Furthermore, OAMdependent transverse and longitudinal pulse shifts of the reflection and refraction of an ST vortex at a planar interface were investigated recently, 27 which may provide a potential method for characterizing ST vortices (Figure 3e).…”
Section: ■ Generationmentioning
confidence: 99%
“…(bottom) Corresponding three-dimensional drawing, in which the reference and ST vortex pulses ( l = 1) are shown next to the camera. Adapted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Characterizationmentioning
confidence: 99%
“…The STOV pulse, therefore, can carry a transverse photonic OAM of l per photon 12 14 Since its discovery, much research has been done in studying STOV pulse, including studying its propagation dynamics, 15 , 16 developing novel characterization approaches, 17 19 utilizing STOV pulse in spatiotemporal imaging, 20 and designing other types of wave packets that also carry transverse photonic OAM 21 25 …”
Section: Introductionmentioning
confidence: 99%